Effects of Zr/Ti ratio on the structure and ferroelectric properties in PZT-PZN-PMN ceramics near the morphotropic phase boundary - R. Muanghlua (2018)
The piezoelectric ceramics of Pb(ZrxTi1-x)O 3 - Pb(Zn1/3Nb2/3)O3 - Pb(Mn 1/3Nb2/3)O3; PZT-PZN-PMN with Zr/Ti ratios of 48/52, 50/50 and 52/48 were fabricated in order to investigate the effect of compositional modifications on the ferroelectric properties of PZT-PZN-PMN ceramics. The phase structure of ceramics sintered at 1,150°C was analyzed. Results show that the pure perovskite phase was in all ceramic specimens, and the phase structure of PZT-PZN-PMN piezoelectric ceramics transformed from tetragonal to rhombohedral, with the Zr/Ti ratios increased in the system. The PZT-PZN-PMN ceramics with a Zr/Ti ratio of 50/50 exhibited the most promising properties including high remanent polarization and low coercive field of 25.95 μC cm-2 and 12.5 kV cm-1, respectively. Furthermore, the transition temperature decreased when the Zr/Ti ratio increased in the system. © 2008 Trans Tech Publications, Switzerland.